Gut Metabolite Trimethylamine-N-Oxide in Atherosclerosis: From Mechanism to Therapy - Wang, BingYu; Qiu, Jun; Lian, JiangFang; Yang, Xi; Zhou, JianQing (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is associated with various pathological manifestations, such as ischemic heart disease, ischemic stroke, and peripheral arterial disease, remaining the leading public health issue. Atherosclerosis is an inflammatory disease characterized by endothelial dysfunction, vascular inflammation, and the deposition of lipids, cholesterol, calcium, and cellular debris within the intima of the vessel wall. The intestinal flora is considered to be a large "secretory organ" of the human body, which produces Trimethylamine oxide (TMAO) by breaking down the food ingested. Studies have shown that TMAO is an independent risk factor for the occurrence of malignant adverse cardiovascular events, but there is controversy about whether there is harm or protective effect on cardiovascular diseases with mild or no clinical manifestations. This article reviews the relationship between TMAO and its precursor (L-carnitine) and coronary atherosclerosis. In addition, we introduce in detail the potential molecular mechanism and therapeutic measures of TMAO on coronary atherosclerosis, in order to provide new ideas for the follow-up study of the pathological mechanism and underlying treatment of coronary atherosclerosis.